Navigating a hyperracialized space: exploring the intersections of whiteness, social control, and mental health in st. louis county, missouri. Issue 5 (4th April 2023) - Jones, Nicole E.; Lewis, Kaleea; Brown, Alaysia M.
ABSTRACT: Places marred by a legacy of racial violence have contemporary implications for racial and ethnic minorities. However, there is limited work examining how racial and ethnic minorities perceive and navigate these spaces and how they may affect their health. We examine the daily lives of Black residents of St. Louis County, living in what we refer to as a hyperracialized space, or areas characterized by multiple forms of violence, to understand how navigating a hyperracialized space impacts how Black residents negotiate space and make meaning of their health. Qualitative interviews (n = 20) revealed three themes: (1) Whiteness and the maintenance of a hyperracialized space, (2) unspoken rules of police encounters and the embodiment of self-regulation, (3) and hypervigilance. Narratives reveal how individuals and institutions concretize a hyperracialized space through social control. Moreover, participants discussed how their environment influenced how they interacted with and navigated space, the toll of which elicited hypervigilance.